The Influence of Ewom, Digital Marketing, Customer Satisfaction and Brand Image on Tiktok Shop Customer Loyalty Student Study in Purwokerto - Layli, Alfina Nur; Hidayah, Arini; Miftahudin, Muhammad Agung; Widhiandono, Hengky (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the influence of Electronic Word of Mouth (EWOM), Digital Marketing, Customer Satisfaction, and Brand Image on customer loyalty within the context of TikTok Shop, a rapidly growing social commerce platform. Using purposive sampling, data were collected from 120 student respondents in Purwokerto via offline questionnaires formatted on a five-point Likert scale. The analysis was conducted using SPSS 26 and comprised descriptive statistics, validity and reliability testing, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression, model fit evaluation, and hypothesis testing. The results indicate that EWOM, Digital Marketing, and Brand Image exert a positive and significant effect on customer loyalty, while Customer Satisfaction shows a negative and significant relationship. These findings suggest that TikTok Shop should enhance its EWOM and digital marketing strategies and reassess its approach to customer satisfaction.